Scaling in Ecology and Biodiversity Conservation - John Pantis (Pensoft Publishers, 2014)
The SCALES book is an attempt to bundle up the main results of SCALES in a comprehensive manner and present it in a way that is usable not only for pure scientists but also for people making decisions in administration, management, policy or even business and NGOs; to people who are more interested in the "practical" side of this issue.